Analysis of Water Pollution in The Musi River Due to Community and Industrial Activities Using Onlimo - Yunita Sari Purba; Uci Sulandari; Lelitasari Lelitasari; Defi Arjuni (Postgraduate, University of Mataram, 2023)
The Musi River is a natural resource which is one of the main trade routes and the largest air supplier for the people of South Sumatra. However, the condition of the Mus River has undergone changes due to dense settlements and industry. Water quality is an important factor in the sustainability of an ecosystem. Ecosystem damage can start from declining air quality which results in industrial waste that pollutes the Musi River. Water quality measurement parameters include measurements of oxygen, TSS, COD, BOD. Observation station sampling was carried out using Onlimo telemetry technology.Â Onlimo is a remote, online and real-time air quality monitoring technology developed by BPPT. Sampling was carried out during the transition season on the Musi River which was divided into station 1 located in the Musi River (PDAM Tirta Randik area, Balui Air Unit, Sanga Desa District). On May 10, 2023 there was a pollution index of 7.32 with moderate contamination with the critical parameters Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD). There was an increase in the Pollution index of 7.51 due to an increase in Nitrate from 16 May 2023 to 17 May 2023 due to input from anthropogenic waste caused by differences in sampling time, besides that season and rainfall are reported to play an important role in dissolving a number of components in the waters. For this reason, to prevent and improve the function of the Musi River, namely the government must act decisively on violations committed by factories or companies or the public who dispose of waste carelessly